Protecting the Future: Enriching reflections on the Covid-19 pandemic from Interdisciplinary Research - Kusuma, Bayu Mitra A. (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2023)
Covid-19 spreads sporadically throughout the world at a high mortality rate. This virus caused a health crisis that forced the World Health Organization to declare it a global pandemic and caused various countries to implement massive social restrictions. Until March 2023, there were 160,963 deaths because of Covid-19, making Indonesia the second highest in Asia. Indonesia's lousy experience managing the Covid-19 pandemic should raise awareness that a crisis can occur at any time. Even though the current situation has improved a lot, preparedness and vigilance should not be neglected. No one can guarantee that a pandemic like Covid-19 will not occur again. Based on this situation, it is essential to look more deeply at the impact of the Covid-19 pandemic and how scholars in various disciplines deal with it. To analyze future risks, interdisciplinary research is needed. This is a research approach that can link the main issues of the medical and health disciplines with other disciplines, such as the environment, social welfare, and public policy.